PENGARUH KARAKTERISTIK DEWAN TERHADAP PENGUNGKAPAN CSR (Studi Empiris Seluruh Perusahaan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017) - Wibowati Sektiyani; Imam Ghozali (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of board characteristics on the possibility of corporate social responsibility disclosure. This study uses secondary data from the company's annual report. The population of this study are all companies listed on the Indonesia Stock Exchange in 2017 while the sample of this study are 175 companies. The sampling method is proportionate stratified random sampling. This study uses a binary logistic regression analysis method. The results of the study showed that the size of the board of commissioners and the number of board of commissioner meetings had a positive and significant effect on corporate social responsibility disclosure. While the independent board of commissioners and the number of women in the board of commissioners have a positive and not significant effect on CSR disclosure.